Comparative analysis of Denosumab and Zoledronic acid in advanced breast cancer patients receiving CDK4/6 inhibitors - Roberta Scafetta; Marco Donato; Carla Gullotta; Alessandra Guarino; Cristina Fiore; Luisana Sisca; Elena Speziale; Raffaella Troiano; Simone Foderaro; Valentina Ricozzi; Michele Iuliani; Sonia Simonetti; et al. (Breast)
A comparative analysis of Denosumab (DMAB) and Zoledronic Acid (ZA) was conducted in a real-world cohort of 864 patients with hormone receptor-positive, human epidermal growth factor receptor 2-negative advanced breast cancer with bone metastases, who were undergoing CDK4/6 inhibitors plus endocrine therapy. We evaluated the time to first skeletal-related events (SREs), progression-free survival (PFS), and overall survival (OS). To adjust for confounding variables, we utilized propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) methodologies. In the unadjusted cohort, ZA was associated with a longer time to first SRE compared to DMAB (HR = 0.77, 95 % CI: 0.61–0.98, p = 0.031). Similar results were obtained in both the PSM (HR = 0.69, 95 % CI: 0.52–0.92, p = 0.011) and IPTW cohorts (HR = 0.74, 95 % CI: 0.63–0.87, p < 0.001), with ZA-treated patients showing an extended time to first SRE compared to those treated with DMAB. No differences in PFS and OS were observed between the two cohorts.